HEALTHCARE-ASSOCIATED INFECTIONS AND MICROBIOLOGICAL ANALYSIS AT THE CLINIC FOR ANESTHESIA AND INTENSIVE THERAPY IN A TERTIARY HEALTH INSTITUTION DURING A ONE-YEAR PERIOD - Stojanovic, Milena (Acta medica Medianae, 2026)
The term Healthcare-Associated Infections (HAI) or Nosocomial Infections (NI) refers to infections that occur in patients during their stay and treatment in medical conditions, but were not present at the time of admission and that manifest at least 48 h after hospital admission. HAIs are more frequent in developing countries (5.7–19.1%) than in developed ones (3.5–12%). Antimicrobial resistance is one of the global health problems with a significant burden, and it is an inevitable consequence of using antimicrobial drugs. The unjustified use of antibiotics has contributed to antimicrobial resistance and changes in the causative pathogens responsible for HAIs. These types of infections prolong the length of hospital stay, lead to long-term disability, and increase morbidity and mortality. The most common types of HAIs are: Ventilator-Associated Pneumonia (VAP), Central Line-Associated Bloodstream Infections (CLABSI), Catheter-Associated Urinary Tract Infections (CAUT) and Surgical Site Infections (SSI). This study aimed to determine the most common bacteria causes of HAIs as well as the distribution according to the type of isolated bacteria from different types of samples. The retrospective study was conducted at the Clinic for Anesthesia and Intensive Therapy, University Clinical Center Niš, during the period from January to December 2024. The patient samples were obtained, namely: blood, groin swab, oral cavity swab, wound swab, rectum swab, armpit swab, urine, aspirate from the endotracheal tube, nose swab, drain content, abdominal cavity content, tip of the central venous catheter, tip of the drain and aspirate from bronchia. The material was sent to the local microbiological laboratory with the aim of obtaining a biogram and antibiogram. Depending on the type of bacteria, the distribution was as follows: Klebsiella spp. (20.15%), Enterococcus faecalis (19.26%), Acinetobacter spp. (14.41%), Pseudomonasaeruginosa (7.9%), Escherichia coli (7.17%), Staphylococcus epidermidis (4.99%), Proteus mirabilis (3.96%), Enterococcus faecium (2.94%), Enterobacter spp. (2.94%) and Staphylococcus spp. (2.19%). Klebsiella spp. was the dominant bacterium isolated from oral cavity swab (3.28%), Enterococcus faecium from groin swab (5.60%), Acinetobacter spp. from endotracheal aspirate (1.91%), Pseudomonas aeruginosa from wound swab (2.25%) and Escherichia coli from rectal swab (1.84%). Healthcare-associated infections have a significant negative impact on hospitalized patients. They lead to permanent disability, prolonged patients’ length of stay and increased mortality as well as expenditure and waste of medical resources. The predominance of microorganisms depends both on the hospital conditions, as well as on the patients and antibiotics prescribed by physicians. It is recommended to establish a precise schedule for antibiotic use in each region based on the most common pathogens and antibiotic resistance patterns, and surveillance programs as important tools which would be helpful to clinicians to choose the most appropriate antimicrobial therapy for hospitalized patients.